Mammographic density and breast cancer risk in Asian women - Mariapun, Shivaani (2024)
Breast cancer is the most common cancer worldwide and in 2020, nearly half of the cases globally were from Asia. The mortality-to-incidence ratio in Asia is higher than the world average, and there is an urgent need to improve early detection of breast cancer and access to curative therapies. Today, early detection of breast cancer is possible through population-based mammography screening, but this is largely unavailable in low- and middle-income countries because of the lack of resources. An alternative approach is to provide screening to those at highest risk, and to explore this possibility, the starting step is to have accurate risk assessment tools for the Asian population.